Emotion and narrative : perspectives in autobiographical storytelling - Habermas, Tilmann (Cambridge : Cambridge University Press, 2019)
Emotions have a life beyond the immediate eliciting situation, as they tend to be shared with others by putting the experience in narrative form. Narrating emotions helps us to express, understand, and share them: the way we tell stories influences how others react to our emotions, and impacts how we cope with emotions ourselves. In Emotion and Narrative, Habermas introduces the forms of oral narratives of personal experiences, and highlights a narrative's capacity to integrate various personal and temporal perspectives. Via theoretical proposals richly illustrated with oral narratives from clinical and non-clinical samples, he demonstrates how the form and variety of perspectives represented in stories strongly, yet unnoticeably, influence the emotional reactions of listeners. For instance, narrators defend themselves against negativity and undesired views of themselves by excluding perspectives from narratives. Habermas shows how parents can help children, and psychotherapists can assist patients, to enrich their narratives with additional perspectives.
Emotions -- Narrative structure -- Narrative evaluations -- Narrative perspectives -- Kinds of emotional effects of narratives -- Narrative perspectives guide recipient emotions -- Context and incongruencies also affect emotional response -- Narratives reflect narrators' ability to bear emotions -- The healing power of narrating -- Working through by narrating experiences repeatedly -- Co-narrating emotional events -- Co-narrating in psychotherapy -- Narrative perspectives in emotions.
Title from publisher's bibliographic system (viewed on 04 Jan 2019).
Keywords: Narration (Rhetoric) -- Psychological aspects; Emotions; Autobiographical memory; Narrative therapy